Manejo da irrigação e adubação nitrogenada no feijoeiro – cultivar TAA DAMA - COUTO, Caio Oliveira Pimenta; LOPES, Adriano da Silva; FRANCO, Jhonatan da Silva; KLIP, Dioph Vitor de Oliveira; MEDEIROS, Rodnei Domingos; MIRANDA, Roger Gomes (ANAIS DO ENIC, 2026)
.